Can a brief session of the online coronavirus disease 2019 destigmatization program reduce stigma among survivors? A randomized controlled trial - Techapoonpon, Kamolvisa; Wonglertwisawakorn, Chayut; Kerdchareon, Nitchawan; Pruttithavorn, Wisarat; Srikhamdokkhae, Orranee (Frontiers in Psychiatry, 2023)
Background: Stigmatization has taken a heavy toll on the mental health and quality of life of the survivors of coronavirus disease 2019 (COVID-19). To address this issue, we proposed a brief, self-directed, reflective, and practical destigmatization intervention. The current study aimed to investigate the efficacy of the online COVID-19 destigmatization program (OCDP) in mitigating stigma among the survivors of COVID-19. Methods: This study was conducted on 142 survivors of COVID-19 before their discharge from Vajra Hospital from July 2022 to November 2022. The participants were randomly assigned between the intervention group (n = 71), who attended the 40-min OCDP, and the control group (n = 71), who received standard mental health care. The primary outcome was the efficacy of OCDP in reducing stigmatization. A COVID-19 stigma questionnaire was administered to assess stigmatization in the intervention and control groups immediately before and after the program during follow-up on days 7, 14, and 28. The secondary outcome was the efficacy of the program in alleviating negative emotions according to the Depression Anxiety Stress Scale 21 questionnaire. Results: Compared with the control group, the intervention group had a more prominent reduction in the overall stigma score on day 7 (p = 0.002) and day 14 (p = 0.028). The intervention group had a more evident reduction in enacted stigma (day 7, p = 0.04), internalized stigma (day 7, p = 0.008; day 14, p < 0.028), and perceived external stigma (day 7, p = 0.002) than the control group. However, there was no significant difference in terms of disclosure concern between the intervention and control groups. Furthermore, the reduction in depression, anxiety, and stress between the two groups did not significantly differ. Conclusion: OCDP provided prior to hospital discharge is an effective tool in reducing stigmatization, particularly within the first 2 weeks after reintegration into society, among the survivors of COVID-19.